2008
DOI: 10.1021/np700718p
|View full text |Cite
|
Sign up to set email alerts
|

Mollamides B and C, Cyclic Hexapeptides from the Indonesian Tunicate Didemnum molle

Abstract: Two new cyclic hexapeptides, mollamides B (1) and C (2), were isolated from the Indonesian tunicate Didemnum molle along with the known peptide keenamide A (3). The structures were established using 1D and 2D NMR experiments. The relative configuration of mollamide B at the thiazoline moiety was determined using molecular modeling coupled with NMR-derived restraints. Their absolute configuration was determined using Marfeyʼs method. The new peptides have been evaluated for their antimicrobial, antimalarial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 22 publications
0
46
0
1
Order By: Relevance
“…Mollamide B exhibited moderate antimalarial activity against P. falciparum (D6 clone and W2 clone), with IC 50 values of 2.0 and 2.1 μg/mL, respectively. Further, mollamide B also exhibited marginal activity against Leishmania donovani , with IC 50 and IC 90 values of 18 and 35 μg/mL, respectively, and against HIV-1 in human PBM cells with an EC 50 value of 48.7 μM [ 83 ].…”
Section: Anti-infective Marine Peptidesmentioning
confidence: 99%
“…Mollamide B exhibited moderate antimalarial activity against P. falciparum (D6 clone and W2 clone), with IC 50 values of 2.0 and 2.1 μg/mL, respectively. Further, mollamide B also exhibited marginal activity against Leishmania donovani , with IC 50 and IC 90 values of 18 and 35 μg/mL, respectively, and against HIV-1 in human PBM cells with an EC 50 value of 48.7 μM [ 83 ].…”
Section: Anti-infective Marine Peptidesmentioning
confidence: 99%
“…Mollamide from Didemnum molle was cyclodepsipeptide and showed cytotoxicity in P388 murine leukemia cells (IC 50 values of 1 μg/mL) and in A549 human lung carcinoma and HT29 human colon carcinoma cells (2.5 μg/mL) ( Figure 40 ) [ 128 , 129 ]. Among these, mollamide B ( 90 ) showed significant percent growth inhibition at 100 μM in the H460 non-small cell lung cancer cell, MCF7 breast cancer cell, and SF-268 CNS cancer cell line, but the National Cancer Institute (NCI) 60-cell line panel lacked tumor cell selectivity [ 130 ]. In contrast to mollamide B, mollamide C ( 91 ) showed strong in vitro cytotoxicity against leukemias (L1210 and CCRF-CEM), solid tumors (38, HCT-116, H125, MCF-7, and LNCaP), and a human normal cell (hematopoietic progenitor cell, CFU-GM); this was observed using a disk diffusion assay.…”
Section: Bioactive Peptides With Anticancer Potential Isolated Fromentioning
confidence: 99%
“…In contrast to mollamide B, mollamide C ( 91 ) showed strong in vitro cytotoxicity against leukemias (L1210 and CCRF-CEM), solid tumors (38, HCT-116, H125, MCF-7, and LNCaP), and a human normal cell (hematopoietic progenitor cell, CFU-GM); this was observed using a disk diffusion assay. The results showed that the leukemia and normal cells were slightly toxic but showed a larger difference in the solid tumor group [ 130 ].…”
Section: Bioactive Peptides With Anticancer Potential Isolated Fromentioning
confidence: 99%
“…[5][6][7] Mollamides are anticancer lead cyanobactins that were isolated in milligrams from ten kilograms of ascidians. [8] As a chemically unrelated example, patellazoles are very potent anticancer polyketides from ascidians, but they cannot be developed because they are rarely found, even in the same location from year-toyear. [9][10][11] This variability promises an almost unlimited source of new bioactive marine natural products.…”
Section: Introductionmentioning
confidence: 99%